Competing Effects of Eastern and Central‐Western Pacific Winds in the Evolution of the 2017 Extreme Coastal El Niño - Sen Zhao; Christina Karamperidou (Geophysical Research Letters)
Abstract In this study, we investigate the relative contributions of dynamical forcings, particularly the eastern and central‐western Pacific winds, and thermodynamical forcings to the evolution of the 2017 extreme coastal El Niño using observations and modeling experiments. We show that the competing effects of anomalous eastern Pacific westerlies and central‐western Pacific easterlies and their resulting downwelling and upwelling equatorial Kelvin waves are essential for the evolution of the event, together with alongshore anomalous northerlies which suppress coastal upwelling and reduce latent heat release as discussed in previous studies. We find that eastern Pacific zonal wind anomalies are about twice as effective in generating a coastal response as central‐western Pacific anomalies, thus compensating for their usually smaller magnitude. While the 2017 event exemplified these competing effects, they were also found to be important in other coastal and basin‐scale El Niño events, thus contributing to the mechanisms responsible for El Niño diversity.